2017
DOI: 10.1097/01.reo.0000000000000071
|View full text |Cite
|
Sign up to set email alerts
|

Oncology Section EDGE Task Force on Cancer: A Systematic Review of Patient-Reported Measures for Sexual Dysfunction

Abstract: Background-Sexual dysfunction is an important and infrequently addressed issue in patients with cancer.Purpose-To identify self-report measures for assessing sexual dysfunction and to evaluate their psychometric properties and relevance to patients with cancer.Methods-Multiple electronic databases (CINAHL, Medline, PsycInfo) were reviewed using specific search terms to locate articles that identify self-report measures assessing sexual dysfunction. From the 1118 articles reviewed, 21 measures were selected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Although it is hard to estimate the prevalence of sexual and relationship difficulties in IBD, one study showed that up to 90% of women surviving gynaecological cancer encountered such difficulties, 16 and 64% of cancer survivors would want HCPs to discuss sexuality issues. 17 Our study brings up for the first time the perspective of IBD patients, who have identified barriers to these conversations which could be classified as being personal, HCP, and environmental barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is hard to estimate the prevalence of sexual and relationship difficulties in IBD, one study showed that up to 90% of women surviving gynaecological cancer encountered such difficulties, 16 and 64% of cancer survivors would want HCPs to discuss sexuality issues. 17 Our study brings up for the first time the perspective of IBD patients, who have identified barriers to these conversations which could be classified as being personal, HCP, and environmental barriers.…”
Section: Discussionmentioning
confidence: 99%
“…The use of validated patient reported measures questionnaires for conducting ecological momentary assessments is well developed and can be used with good design in terms of frequency and response burden [69,70]. Patient reported experience and outcomes measures (PREMS and PROMS) have been developed in a variety of disease areas and are a promising way for mhealth app developers to get a jump start on ecological momentary assessments [71][72][73][74]. Use of PREMS and PROMS may incur a license fee but are worth the cost since the tools are generally validated and are widely used in clinical trials.…”
Section: Ecological Momentary Assessments and Interventions Are Usefu...mentioning
confidence: 99%
“…Changes in intimacy and sexuality can arise due to the cancer itself, the treatment or psychological and social factors such as anxiety or distress [ 13 ]. For instance, cancer treatment might cause problems with sexual desire and arousal problems [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%